The Botram Harmony Tradition: Knitting a Harmonious Life in Frames Islamic Moderation - Firdaus, Muhamad Yoga; Assauri, Muhamad Farhan; Taqiyya Haqqi, Nurul Aziza (Jurnal Penelitian Ilmu Ushuluddin, 2023)
This research explains that the Botram Harmony Tradition is a social glue that promotes harmony and removes social discord. The Botram Harmony custom celebrates religious festivals by sharing a communal lunch with all religious groups. Local religious authorities started this ritual and funded it with udunan income. Qualitative and descriptive Qur'an thematic studies are used in this research. A critical and comprehensive investigation of the Botram Harmony tradition may solve Indonesia's socio-religious issues, including intolerance and extremism. This study found that the Harmony Botram tradition embodies the Islamic washatiyah precept that diversity is beautiful. Then, the Botram Harmony tradition may promote unity, harmony, and societal issues like intolerance and extremism. This study just covers Botram Harmony. As a result, it is expected that multicultural Indonesia will develop new social connecting techniques.